2021
DOI: 10.1002/pros.24210
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of two novel cell line models of castration‐resistant prostate cancer

Abstract: Background Resistance to androgen deprivation therapies is a major driver of mortality in advanced prostate cancer. Therefore, there is a need to develop new preclinical models that allow the investigation of resistance mechanisms and the assessment of drugs for the treatment of castration‐resistant prostate cancer. Methods We generated two novel cell line models (LAPC4‐CR and VCaP‐CR) which were derived by passaging LAPC4 and VCaP cells in vivo and in vitro under castrate conditions. We performed detailed tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Both hormone sensitive cell lines, LNCaP and VCaP, demonstrate altered ORR responses to metabolic inhibitors after ADT compared to control conditions (Figure 4B,C). Responses demonstrate some variation between lines which is unsurprising due to their different genetic phenotypes 48 . LNCaP cells in FBS control conditions show altered ORR (normalized to the media control) for all metabolic inhibitors (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both hormone sensitive cell lines, LNCaP and VCaP, demonstrate altered ORR responses to metabolic inhibitors after ADT compared to control conditions (Figure 4B,C). Responses demonstrate some variation between lines which is unsurprising due to their different genetic phenotypes 48 . LNCaP cells in FBS control conditions show altered ORR (normalized to the media control) for all metabolic inhibitors (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has investigated AR antagonists after ADT and observed similar signaling responses, 6,33 here, we focus on targeted metabolic inhibitors. Differences in responses to metabolic inhibitors was noted between hormone‐sensitive cell lines, reflecting the genetic and perhaps epigenetic heterogeneity of PC 48,54 . Importantly, OMI of two hormone sensitive lines showed that ADT‐treated cells were resistant to several targeted metabolic inhibitors, most notably inhibition of FA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen treatment rapidly stimulates the transcription of hundreds to thousands of protein-encoding genes, but moreover, represses a number of genes, with a considerable overlap between different hormone-dependent prostate cancer cell lines [ 85 , 167 , 168 , 169 ]. A number of non-coding transcripts are also directly regulated by the AR [ 149 ].…”
Section: Transcriptomementioning
confidence: 99%
“…Chromogranin A (CgA) is an acidic glycoprotein commonly expressed in all neuroendocrine cells and serum levels are increased in patients with neuroendocrine tumors 7 . Neuroendocrine activity can also be detected in prostate cancer as a marker of its neuroendocrine differentiation; more specifically, CgA levels are elevated in castration‐resistant PCa patients 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…7 Neuroendocrine activity can also be detected in prostate cancer as a marker of its neuroendocrine differentiation; more specifically, CgA levels are elevated in castrationresistant PCa patients. [8][9][10][11] In recent years, the prognostic capacity of CgA as a biomarker for PCa has been extensively evaluated. Hong et al in their recent meta-analysis indicated that having high CgA levels represents an independent predictor of worse overall survival (OS) and progression-free survival (PFS) in castration-resistant prostate cancer (CRPC) patients.…”
Section: Introductionmentioning
confidence: 99%